Ultrasound microbubbles-mediated miR-216b affects MALAT1-miRNA axis in non-small cell lung cancer cells. (February 2022) - Wang, Jian; Mo, Jianming; Xie, Yuancai; Wang, Chunguang
Highlights: MiR-216b was restrained and MALAT1 was enhanced in NSCLC tissues, and miR-216b was negatively bound to MALAT1. UTMBs-mediated M restrained the cell biological behaviors by repressing MALAT1. Ultrasound microbubbles-mediated miR-216b could affect the downstream multiple miRNAs of MALAT1. Abstract: MiR-216b is ectopically expressed in various cancers. Ultrasound microbubbles (UTMBs) are an effective method for miRNA delivery. This article mainly explored the involvement of lncRNA in the effects of UTMBs-mediated miR-216b on non-small cell lung cancer (NSCLC) progression. Expressions and relationship of miR-216b and MALAT1 were examined using quantitative real-time polymerase chain reaction (qRT-PCR), Pearson, TargetScan, and dual-luciferase reporter assay. After the transfection with liposome- or UTMBs-mediated miR-216b mimic (M) or MALAT1 overexpression plasmid alone or together, levels of miR-216b and MALAT1, cell biological behaviors, as well as expressions of apoptosis- and epithelial mesenchymal transition (EMT)-related markers were examined using qRT-PCR, cell functional experiments, and western blot. Besides, we used qRT-PCR to quantify the expressions of multiple downstream miRNAs of MALAT1. MiR-216b expression was weakened yet MALAT1 expression was enhanced in NSCLC tissues, and miR-216b was negatively bound to MALAT1. TargetScan analysis manifested that miR-216b, targeted by MALAT1, was down-regulated in NSCLC cells. UTMBs-mediated miR-216b M further intensified miR-216b level yet weakened cell biological behaviors. The inhibitory effect of UTMBs-mediated miR-216b M on cell biological behaviors and MALAT1 expression was greatly better relative to that of miR-216b M. Moreover, miR-216b restrained the cell biological behaviors by repressing MALAT1 expression. We further manifested that miR-216b facilitated the expressions of apoptosis-related markers, but restrained those of EMT-related markers by repressing MALAT1 expression. Moreover, UTMBs-mediated miR-216b M enhanced the expressions of downstream multiple miRNAs of MALAT1, but this tendency was reversed by co-transfection of overexpressed MALAT1 and miR-216b M. Collectively, UTMBs-mediated miR-216b M restrained NSCLC cell growth by modulating the MALAT1-miRNA axis.